MATRIX FLUX POTENTIAL BEBERAPA JENIS TANAH HOMOGEN PADA MASALAH INFILTRASI STASIONER DARI SUATU SALURAN IRIGASI TUNGGAL - Munadi, Munadi; Isnani, Isnani; Oktaviani, Dian Nataria; Utami, Wikan Budi; Ariwibowo, M. Dwi (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
ABSTRACT. In this paper, we study the problem of stationary infiltration on several types of homogeneous soil from a single trapezoidal channel. A governing equation in this problem is in the form of a nonlinear differential equation and is called the Richards’ equation. The equation can be solved more easily by transforming it into a modified Helmholtz equation. In this study, the Dual Reciprocity Boundary Element Method (DRBEM) was used to solve the modified Helmholtz equation numerically. Then, using the obtained solution, the numerical values of the Matric Flux Potential (MFP) for each soil type were computed and then compared. For the position of the same points, the Pima Clay Loam soil type has the highest MFP value, followed by Clay Loam and Sandy Loam.Keywords: Richards’ equation, modified Helmholtz equation, matric flux potential, DRBEM, single irrigation channel. ABSTRAK. Dalam artikel ini dibahas masalah infiltrasi stasioner pada beberapa jenis tanah homogen dari saluran irigasi tunggal bentuk trapesium. Persamaan pengatur masalah ini berbentuk persamaan diferensial nonlinear dan disebut dengan persamaan Richards. Persamaan tersebut dapat diselesaikan lebih mudah dengan mentransformasikannya menjadi persamaan Helmholtz termodifikasi. Dalam artikel ini, Dual Reciprocity Boundary Element Methods (DRBEM) digunakan untuk menyelesaikan persamaan Helmholtz termodifikasi tersebut secara numerik. Selanjutnya, dihitung nilai numerik Matric Flux Potential (MFP) masing-masing jenis tanah dan kemudian dibandingkan. Untuk posisi titik-titik yang sama, jenis tanah Pima Clay Loam mempunyai nilai MFP tertinggi, kemudian disusul oleh Clay Loam dan Sandy Loam. Kata Kunci: persamaan Richards, persamaan Helmholtz termodifikasi, matric flux potential, DRBEM, saluran irigasi tunggal.